Draft Genome Sequence of Neisseria gonorrhoeae Strain NG_869 with Penicillin, Tetracycline and Ciprofloxacin Resistance Determinants Isolated from Malaysia - Ang, G.Y.; Yu, C.Y.; Yong, D.A.; Cheong, Y.M.; Yin, Wai Fong; Chan, Kok Gan (Springer Verlag (Germany), 2016)
Gonorrhea is a sexually transmitted infection caused by Neisseria gonorrhoeae and the increasing reports of multidrug-resistant gonococcal isolates are a global public health care concern. Herein, we report the genome sequence of N. gonorrhoeae strain NG_869 isolated from Malaysia which may provide insights into the drug resistance determinants in gonococcal bacteria.